Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/slct.201802810
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Gadolinium(III)‐Oligopeptide Complexes and Carbon Nanotube Composite as Dual Modality Anticancer Agents

Abstract: In search of non-platinum based anticancer drugs, we have synthesized and characterized a new class of three gadoliniumand a carbon nanotube composite, 1@CNT 4. The three oligopeptides, L 1 -L 3 were prepared in a novel synthetic route using tetramethyl benzotriazolyl uronium hexaflurophosphate (HBTU) as a peptide coupling reagent. Confocal microscopic analysis of the gadolinium(III)-oligopeptides, 1, 2 and CNT composite, 1@CNT 4 indicate that they display white and green light emissions upon excitations at λ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 66 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…In this context, CNTs offer an opportunity to shelter anti-cancer drugs thus lowering their toxicity for an organism and enhancing local accumulation in the desired site. Up to date, different types of anti-cancer compounds have been proposed and tested in regards their conjunction and functionality with the CNTs [66,67].…”
Section: Carbon Nanotubes In Cancer Treatmentmentioning
confidence: 99%
“…In this context, CNTs offer an opportunity to shelter anti-cancer drugs thus lowering their toxicity for an organism and enhancing local accumulation in the desired site. Up to date, different types of anti-cancer compounds have been proposed and tested in regards their conjunction and functionality with the CNTs [66,67].…”
Section: Carbon Nanotubes In Cancer Treatmentmentioning
confidence: 99%
“…Chemotherapy leads to the death of cancer cells along with normal cells instigating serious side effects. Considering these hindrances, CNTs can protect the chemotherapeutics, and in turn, lower their toxicity toward normal tissues by localizing the drug at the target site [78,79]. Their interaction with lipid membranes and intracellular transport mechanism is inadequately understood, but few studies have suggested that CNTs enter cells via various endocytic processes [80,81].…”
Section: Cnts For Drug Deliverymentioning
confidence: 99%
“…In all the previously discussed findings, the proposed therapeutic doses are much lower than the "onetenth" portion of the STD 10. Accordingly, the therapeutic doses can be reduced to be equal or below the micromolar concentrations recommended by many researches [54,56] 4.…”
mentioning
confidence: 99%